Loncastuximab tesirine in relapsed or refractory diffuse large B-cell lymphoma (LOTIS-2): a multicentre, open-label, single-arm, phase 2 trial. Issue 6 (June 2021) - Caimi, Paolo F; Ai, Weiyun; Alderuccio, Juan Pablo; Ardeshna, Kirit M; Hamadani, Mehdi; Hess, Brian; Kahl, Brad S; Radford, John; Solh, Melhem; Stathis, Anastasios; Zinzani, Pier Luigi; Havenith, Karin; et al.
Summary: Background: Patients with relapsed or refractory diffuse large B-cell lymphoma (DLBCL) who do not respond to or who have progressive disease after salvage therapies have a poor prognosis. Loncastuximab tesirine is a CD19-directed antibody–drug conjugate with encouraging phase 1 single-agent antitumour activity and acceptable safety in non-Hodgkin lymphoma. We aimed to evaluate the antitumour activity and safety of loncastuximab tesirine in patients with relapsed or refractory DLBCL. Methods: We did a multicentre (28 hospital sites in the USA, UK, Italy, and Switzerland), open-label, single-arm, phase 2 trial (LOTIS-2) in patients aged 18 years or older with relapsed or refractory DLBCL after two or more multiagent systemic treatments, who had measurable disease and Eastern Cooperative Oncology Group performance status 0–2. Eligible patients received loncastuximab tesirine intravenously on day 1 of each 21-day cycle, at 150 μg/kg for two cycles, then 75 μg/kg thereafter, for up to 1 year or until disease relapse or progression, unacceptable toxicity, death, major protocol deviation, pregnancy, or patient, investigator, or sponsor decision. The primary endpoint was overall response rate assessed by central review. Primary antitumour activity and safety analyses were done in the as-treated population (patients who received at least one dose of loncastuximab tesirine), when all responding patients had at least 6 months of follow-up after initial documented response. Enrolment is complete. This trial is registered with ClinicalTrials.gov, NCT03589469 . Findings: Between Aug 1, 2018, and Sept 24, 2019, 184 patients were assessed for eligibility and 145 (79%) were enrolled and received at least one dose of loncastuximab tesirine, including patients with high-risk characteristics for poor prognosis, such as double-hit, triple-hit, transformed, or primary refractory DLBCL. 70 of 145 patients had complete or partial response (overall response rate 48·3% [95% CI 39·9–56·7]); 35 had complete response and 35 had partial response. The most common grade 3 or higher treatment-emergent adverse events were neutropenia (37 [26%] of 145 patients), thrombocytopenia (26 [18%]), and increased gamma-glutamyltransferase (24 [17%]). Serious adverse events were reported in 57 (39%) of 145 patients. Treatment-emergent adverse events with a fatal outcome occurred in eight (6%) of 145 patients; none were considered related to loncastuximab tesirine. Interpretation: Loncastuximab tesirine has substantial single-agent antitumour activity and produces durable responses with an acceptable safety profile, potentially offering a new therapeutic option for heavily pretreated patients with relapsed or refractory DLBCL. Funding: ADC Therapeutics.